Effect of Strong El-Nino and Strong La-Nina Periode on Groundwater Availability in Palembang City - Rezfiko Agdialta (Sriwijaya Journal of Environment, 2019)
El-Nino results in reduced air mass in most parts of Indonesia and can cause drought. In the La-Nina phase some parts of Indonesia will get more water vapor resulting in increased frequency of rain. Increased rainfall has an impact on  groundwater availability. Groundwater  availability illustrates the condition of water in the soil which is useful in many sectors of life, especially in the agricultural sector. This study aims to see the relationship between the El Nino and La Nina phenomena strongly by using SOI indicators on groundwater availability in Palembang. In the Strong El-Nino phase in 1994 and 1997 the SOI index had a moderate correlation with  groundwater availability of 32% and 39%. In 2015 the correlation of SOI to groundwater avability was 79% indicating a strong relationship. In 2008 and 2011 which was a strong La-Nina phase the SOI index correlation value for groundwater availability was 46% and 45%, respectively, which indicated a moderate correlation.